Responses of Morphology, Gas Exchange, Photochemical Activity of Photosystem II, and Antioxidant Balance in Cyclocarya paliurus to Light Spectra - Liu, Yang; Wang, Tongli; Fang, Shengzuo; Zhou, Mingming; Qin, Jian (Frontiers in Plant Science, 2018)
Light quality is a critical factor regulating photosynthetic capacity which directly affects the final yield of plants. Cyclocarya paliurus is a multiple function tree species and its leaves are widely used as tea production and ingredient in functional foods in China. However, the effects of varying light quality on photosynthetic process and the photoprotective mechanisms remains unexplored in-depth. In this study, the biomass accumulation, morphology changes, photosynthetic capacity, stomata ultrastructure, pigments content, PSII activity, reactive oxygen species production, antioxidant enzymes, and phenolic content of C. paliurus plants under different light-emitting diodes (LED) light treatments were investigated to test a hypothesis that the difference in photosynthetic efficiency of C. paliurus plants under differential light quality is related to the degree of photoinhibition and the activation of photoprotection. We found that C. paliurus plants performed better under the treatments of WL (white light, 445 and 560 nm) and BL (blue light, 456 nm) than the treatment of GL (green light, 514 nm) and RL (red light, 653 nm). The better performances were characterized by higher values of photosynthetic capacity, total biomass, pigments content, specific leaf mass per area, seeding height increment, leaf thickness and palisade length. In contrast, plants under the treatments of GL and RL suffered significant photoinhibition but effectively developed photoprotective mechanisms. Results of this study provide not only some insights of the response mechanisms of plant photosynthesis to light quality but also a scientific basis for improving the cultivation of C. paliurus plantations.